Efficacy and safety of guanxinshutong capsule combined with western medicine on stable angina pectoris: a systematic review and meta-analysis - Yu, Liyuan; Wu, Lulu; Peng, Weihang; Huang, Peiying; Chen, Li; Deng, Yi; Wang, Meida; Zeng, Jing; Chen, Bojun (Frontiers in Pharmacology, 2024)
Aims: To systematically evaluate the efficacy and safety of the GXST combined with WM in treating stable angina pectoris (SAP). Methods: RCTs evaluating the efficacy of GXST combined with WM for the treatment of patients with SAP were searched across several databases, including the Cochrane Library, PubMed, Embase, the Chinese National Knowledge Infrastructure (CNKI), the Chinese Science and Technology Journal Database (VIP), and Wan Fang, from inception until April 30, 2024. Two independent reviewers rigorously performed study selection, data extraction, and quality assessment. Version 2 of the Cochrane risk-of-bias tool for randomized trials (RoB 2) was employed to assess the methodological quality of included RCTs. R version 4.2.2 was applied for data synthesis. Results: Between 2012 and 2024, 31 RCTs involving 4,172 patients were identified, with 2,101 in the experimental group and 2,071 in the control group. GXST and WM combination was significantly more effective than WM alone across several metrics: clinical efficacy rate (odds ratio [OR] = 4.05, 95% confidence interval [CI] = 3.42 to 4.80), electrocardiogram improvement (OR = 3.39, 95% CI = 2.35 to 4.87), enhancement in left ventricular ejection fraction (mean difference [MD] = 1.07, 95% CI = 0.69 to 1.46), reduction in total cholesterol levels (MD = -0.78, 95% CI = -1.20 to -0.35), decrease in tumor necrosis factor-alpha (MD = -1.36, 95% CI = -2.18 to -0.53), and improvement in Chinese medicine evidence score (OR = 3.77, 95% CI = 2.20 to 6.43). No significant difference was observed in the reduction in C-reactive protein levels (MD = -6.66, 95% CI = -15.91 to 2.59), triglyceride levels (MD = -1.62, 95% CI = -3.39 to 0.15), or in the occurrence of adverse drug reactions (OR = 0.60, 95% CI = 0.23 to 1.57). Based on metaregression and subgroup analyses, the observed heterogeneity was attributed to variations in GXST capsule dosage, the duration of treatment, and the baseline characteristics of patients. Conclusion: GXST and WM combination therapy demonstrates the potential to enhance clinical outcomes for SAP patients. Nevertheless, additional rigorous studies are imperative to substantiate the reliability and safety of this combined treatment modality.